Stray city : a novel - Johnson, Chelsey, 1975- (Custom House, 2018)
"A hilarious and heartfelt coming-of-age and modern family drama, set in the queer underground of late 90s Portland, that explores the complications of belonging--to a city, a culture, and a family--and what happens when those forms can't quite contain who you really are"--